To forget it all and begin anew : reconciliation in Occupied Germany, 1944 - 1954 - Schroeder, Steven M. 1969- (German and European studies ;, 2013)
"Germany's transition from Nazism to peaceful, if at times reluctant, integration into the western and Soviet spheres during the decade immediately following the Second World War is one of the most remarkable events of the twentieth century. Shattered relations between Germans and their wartime enemies and victims had rendered prospects for peaceful relations between these groups unimaginable, or a dream belonging to the distant future. However, numerous grassroots initiatives found varying degrees of success in fostering reconciliation. Drawing on underutilized archival materials, To Forget It All and Begin Anew reveals a nuanced mosaic of like-minded people - from Germany and other countries, and from a wide variety of backgrounds and motives - who worked against considerable odds to make right the wrongs of the Nazi era. While acknowledging the enormous obstacles and challenges to reconciliatory work in postwar Germany, Steven M. Schroeder highlights the tangible and lasting achievements of this work, which marked the first steps toward new modes of peaceful engagement and cooperation in Germany and Europe."--Publisher's description